Frugivory by phyllostomid bats (Mammalia: Chiroptera) in a restored area in Southeast Brazil - Silveira, Maurício [UNESP]; Trevelin, Leonardo [UNESP]; Port-Carvalho, Marcio; Godoi, Simone; Mandetta, Elizabeth Neuenhaus [UNESP]; Cruz-Neto, Ariovaldo P. [UNESP] (Elsevier, 2011)
We studied the potential contribution of frugivorous bats to the reestablishment of vegetational diversity in a restored area. We analysed the diets of the bat species and the differences between them in the consumption of fruits of autochtonous and allochthonous species. Planted (autochtonous) species were the basis of diets, especially Solanum mauritianum and Cecropia pachystachya, whereas for allochthonous species we found that Piperaceae to be of particular importance. Carollia perspicillata was the main seed disperser for allochthonous species, and potentially the most important bat in the promotion of vegetation diversity in the study area. Our results suggest that frugivorous bats are especially important in the reestablishment of vegetation in disturbed areas, and that restorarion efforts should focus on the planting of different zoochorous species that would guarantee a high year-round fruit production, thereby facilitating natural plant reestablishment by frugivorous bats in regenerating areas. © 2010 Elsevier Masson SAS.
Keywords: Diet; Ecological restoration; Frugivorous bats; Seed dispersal; Semi deciduous forests; allochthon; autochthon; bat; deciduous forest; dicotyledon; frugivory; fruit production; restoration ecology; seed dispersal; Brazil; Carollia perspicillata; Cecropia; Cecropia pachystachya; Chiroptera; Mammalia; Phyllostomidae; Piperaceae; Solanum; Solanum mauritianum